Peningkatan Hasil Belajar Peserta Didik Kelas II Mata Pelajaran Matematika Materi Pengukuran Melalui Metode The Power Of Two Four di SD 30 Sumpang Bita Kecamatan Balocci Kabupaten Pangkajene - Nurislamiah, Fauzia; Nurhaliza Septiyani Muhtar, Indah; Zahra Amalia Faisal, Sitti (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The research carried out was a class action research (CAR) which aimed to find out the increase in student learning outcomes through the Power Of Two And Four method of mathematics subject matter of time measurement for Class II students at SD 30 Sumpang Bita, Balocci District, Pangkajene Regency. This research was conducted in two cycles which included four meetings. The subjects of this study were 12 students of Class II SD 30 Sumpang Bita, Balocci District, Pangkajene Regency, including 6 boys and 6 girls. Data collection techniques are observation, test (evaluation), and documentation. The data obtained were then analyzed using quantitative and qualitative descriptive analysis. The research results at the pre-cycle stage averaged 59.37 with a percentage of 54.17%, which means that they did not meet the criteria. In cycle I obtained an average of 71.87, with a percentage of 83.33%. In this cycle I have fulfilled the KKM but in reality there are still some students who have not completed it so it is necessary to hold the next cycle. In the second cycle, the average score is 82.5 with a percentage of 91.67%. This means that the research at this stage is quite perfect because all students have fulfilled the KKM. From the results of this analysis it was concluded that the learning outcomes of mathematics in Grade II students at SD 30 Sumpang Bita, Balocci District, Pangkajene Regency could be improved through The Power Of Two And Four method.